Natural and Waste Hydrocarbon Precursors for the Synthesis of Carbon Based Nanomaterials: Graphene and Cnts - Singh, D (Elsevier Ltd, 2016)
Carbon nanomaterials have huge potential in the field of energy and environmental applications. However, a wide range of greener and environment friendly synthesis methods utilizing natural, renewable, cheaper waste materials has to be developed. This will lead to the reduction of green house gases, exploitation of toxic materials and helps in the development of sustainable technologies. In this review, the details progress made in the last ten years concerning the synthesis of new one dimensional (carbon nanotubes CNT, carbon nanofiber) and two dimensional (graphene) carbon based materials using natural precursors and waste materials is summarized. The aim of this review paper is to provide a comprehensive scientific progress of synthesis of graphene and carbon nanotubes using natural precursor and waste materials for the future perspective. This paper also concludes with a brief discussion on the impact of natural precursor for the graphene and CNTs for environment, its toxicological effects and its future prospects in this rapidly emerging field. Natural precursors and waste carbon containing products are emerging as a new class of materials that have efficiency to produce graphene and CNTs. The various synthesis processes of graphene, CNTs and carbon dots has been reported using several natural hydrocarbon precursors (turpentine oil, eucalyptus oil, palm oil, neem oil, sunflower oil, castor oil, biodiesel, tea-tree extract, honey, milk, sugar, butter, egg etc.). Also, some research groups have used foods wastes (cookie and chocolate), vegetation wastes (woods, leaf, grass, fruit wastes), animal/bird/insect wastes (bone and cow dung, dog feces, chicken feather) and agro waste (sugarcane bagasse) for the synthesis of graphene and CNTs. Research on natural hydrocarbon precursors and wastage materials has increased in recent years as they promise to produce better and high quality of graphene and CNTs in large quantities. The fascinating aspect of this research area is that it guides the use of natural hydrocarbons to explore the possibilities of improving graphene stability and robustness suitable for different type of applications. © 2015 Elsevier Ltd. All rights reserved.